Calibration of Nonstationary Gas Sensors Based on Two-Dimensional Materials - Duesberg, Georg (My University, 2020)
Two-dimensional materials (2DMs) have high potential in gas sensing, due to their large surface-to-volume ratio. However, most sensors based on 2DMs suffer from the lack of a steady state during gas exposure, hampering sensor calibration. Here, we demonstrate that analysis of the time differential of the signal output enables the calibration of chemiresistors based on platinum or tungsten diselenide (PtSe2, WSe2) and molybdenum disulfide (MoS2), which present nonstationary behavior. 2DMs are synthesized by thermally assisted conversion of predeposited metals on a silicon/silicon dioxide substrate and therefore are integrable with standard complementary metal-oxide semiconductor (CMOS) technology. We analyze the behavior of the sensors at room temperature toward nitrogen dioxide (NO2) in a narrow range from 0.1 to 1 ppm. This study overcomes the problem of the absence of steady-state signals in 2DM gas sensors and thus facilitates their usage in this highly important application.
Keywords: silicon/silicon dioxide substrate; Two-dimensional materials (2DMs); gas sensing